Virtual environments design assessment for the treatment of claustrophobia - Christofi, Maria; Michael-Grigoriou, Despina (My University, 2017)
Virtual reality exposure therapy (VRET), can help the lives of many people. Its advantages over other treatment methods for psychological disorders and more specifically phobias, like its cost effectiveness and control, make it the method that we should focus on. Claustrophobia is the phobia that we have studied. Creating suitable claustrophobic virtual environments (VEs) for patients to get immersed in, is crucial if we want to eventually treat them only with the use of VRET. We designed and developed a virtual reality (VR) framework that allows us to investigate whether VR can reproduce anxiety due to claustrophobic aspects and investigate which characteristics of the virtual environments design contribute to this. Three characteristics (space openness, tidiness and color) have been investigated through this study with our results indicating that they may affect the feeling of anxiety.
Keywords: Claustrophobia; Virtual environments; Virtual Reality